FAKTOR-FAKTOR YANG MEMPENGARUHI BEHAVIORAL INTENTION TO USE PENGGUNAAN SOFTWARE AKUNTANSI PADA UMKM - Nina Ayu Kusuma Wardani; Iwan Setya Putra (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2022)
This study aims to know the factors influencing the behavioral intention to use accounting software in MSMEs in Blitar Regency. Those factors were perceived ease of use, perceived usefulness, and attitude toward using in the Technology Acceptance Model. This type of research used quantitative research and data collection techniques through a questionnaires given to MSME actors in the Blitar Regency area. Used the Slovin formula, the samples taken in this study were 400 respondents. Method of data analysis used validity test, reliability test and path analysis. The results of this study indicated that perceived ease of use and perceived usefulness significantly affected attitudes toward using the use of accounting software in MSMEs in Blitar Regency. The perceived ease of use and perceived usefulness also affected behavioral intention to use accounting software use in MSMEs in Blitar Regency either through intermediaries or direct. Lastly, attitude toward using significantly affected behavioral intention to use accounting software in MSMEs in Blitar Regency as well.